Şeyhî dîvânı’nda tıbbî unsurlar - Günan, Merve (My University, 2018)
Şeyhî, 15. yüzyılın önemli şâirlerinden ve hekimlerinden biridir ve klasik Türk şiirinin kurucularından kabul edilir. Bu çalışmada onun divanında yer verdiği tıbbî unsurlar incelenmiştir. Çalışma, dört bölümden oluşmaktadır. Her bölümde konuyla ilgili bilgi verilmiş ve o hususun yer aldığı beyitlerden örnekler nesre çevirileriyle birlikte sunulmuştur. Çalışmanın amacı; Şeyhî’nin, şiirlerinde meslek alanı olan tıpla ilgili unsurlara ne şekilde yer verdiğini tespit etmektir.

Şeyhî, is one of the most important poets and physicians of the 15th century and is accepted by the founders of classical Turkish poetry. In this study, the medical elements of his divan were examined. The study consists of four parts. In each section, relevant information was given on the subject, and examples from the couplets in which the matter is included are presented with the translation of the prose. Purpose of the study; It is to determine how Şeyhî's place in poetry is related to the elements of poetry, which is the profession.
Keywords: 15 th century; 15. yy; 15th Century; Biography; Biyografi; Divan; Divan poetry; Divan şiiri; Edebiyat ve tıp; Hekimler yazar olarak; History; Literature and medicine; medicine; Medicine in Literature; meslek; Physicians as authors; Poets, Turkish; profession; Şairler, Türk; Şeyhî; Şeyhî, 15. yy; Şeyhî, 15th century; Tarih; tıp; Tıp, Edebiyatta; Turkey; Turkish literatıre; Turkish poetry; Türk edebiyatı; Türk şiiri; Türkiye